The effect of tourism source market structure on international tourism revenues in Turkey. Issue 3 (May 2022) - Ağazade, Seymur
The current study calculates an indicator of tourism source market structure and investigates its impact on international tourism revenues in Turkey. This structure may influence the tourism performance through its consequences on the competitiveness and risk structure of the sector. The calculation of tourism source market structure in this study is based on the normalized Herfindahl–Hirschman Index and number of tourists by nationality. The ARDL co-integration framework is the method used and the estimation covers the period between January 2008 and September 2019. The calculated tourism source market structure indicator showed decreasing trend in the research period indicating that the tourism source market diversified in some extent. The co-integration is supported, and in the long-term model a 1% decrease in the tourism source market concentration found to increase international tourism revenues by 1.9078%. Furthermore, the error correction model indicated that it takes 7.16 months for deviations from the long-run relationship to return to the equilibrium.